Impact of transferring Japanese human resource management concepts to worklife balance of the Filipino employees - Serrano, Christine Joy Del Rosario (Animo Repository, 2010)
This paper investigated the impact of transferring Japanese human resource management concepts to worklife balance of the employees. Specifically, the study identified if there is a relationship among Japanese human resource management concepts of lifetime employment and seniority system, Hofstedes cultural dimensions such as power distance and individualism and worklife balance. The descriptive research design employing both qualitative and quantitative approach was used. All employees of Company X ware requested to answer the survey and the management of the company were asked to give their suggestion and recommendation based on the result of the study. Multiple correlation and regression were used to answers the problems of the study. It was found out that there is a relationship between Japanese Human Resource Management concepts of lifetime employment and seniority system, Hofstedes cultural dimensions such as power distance and individualism and worklife balance. The significant relationships are between worklife balance and lifetime employment, worklife balance and seniority system, worklife balance and individualism, individualism and lifetime employment, individualism and seniority system, and power distance and lifetime employment. Finally, based from the result of the study the company needs to undergo the process of acculturation, to establish career development programs and to initiate worklife balance programs.